Análise de radionuclídeos naturais e artificiais do solo e de produtos alimentícios no Estado de Sergipe, principalmente na região do Platô de Neópolis (SE) - Cardoso, Leandro Xavier (2012)
Measurements of radioactivity in the environment are of great importance in monitoring and control of radiation levels to which humans are exposed directly or indirectly. Two nuclear power plants are planned in the northeast Brazilian region by the Ministry of Mines and Energy under the National Energy Plan 2030. Even without defining the exact location were these new plants would be built; there is great speculation that new units will soon be built along the banks of the San Francisco River. This region is extremely poor in studies from the standpoint of determining the type of radionuclide and radioactivity in the environment, being practically non-existent in the literature data on the state of Sergipe. This study aimed to contribute to analysis of the occurrence of natural and artificial radioactive material in soil, water and food products of the State of Sergipe, focusing primarily on Neópolis Plateau region, which is located the banks of the Rio San Francisco. For this purpose, radionuclides found in all samples collected from soil and cement, fertilizer and food chain products were analyzed by gamma spectrometry, whose activity was measured employing a HPGe detector. The highest activity was determined due to K-40 (1636 + 35) ´ 10 Bq.kg-1 in KCl fertilizer, and the lowest activity was due to Bi-212 (0.001 + 0.009) Bq.kg-1 in lemon peel. The activities of radionuclides measured in all samples are below the Brazilian criteria for exclusion, exemption and waiver required for protection against radiation. Be-7 was detected in organic fertilizers and lemon peel and Th-232 found in samples of soil and cement in the state of Sergipe, both unprecedented results in the literature. It was also detected Cs-137 in some samples, probably from fertilizers and food additives imported from northern countries, yet their activities do not pose a risk to the population.